The personal distribution of incomes - Atkinson, A. B.; Royal Economic Society (Great Britain) (London : George Allen & Unwin, 1976)
This volume contains the various conference papers on the personal distribution of incomes and earnings, including comparisons of the distribution found in different periods and societies.
Papers presented at the Royal Economic Society's conference on the personal distribution of incomes and property, held between 1-5 July, 1974.
Includes bibliographical references and index.
osa16/08/2017
Loans
Keywords: Income distribution